2022
DOI: 10.1186/s12877-022-02839-5
|View full text |Cite
|
Sign up to set email alerts
|

Social support and subsequent cognitive frailty during a 1-year follow-up of older people: the mediating role of psychological distress

Abstract: Background Frailty and cognitive impairment are two common geriatric symptoms linking adverse health-related outcomes. However, cognitive frailty, a new definition defined by an international consensus group, has been shown to be a better predictor of increased disability, mortality, and other adverse health outcomes among older people than just frailty or cognitive impairment. This study estimated the prospective association between social support and subsequent cognitive frailty over 1 year f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…In a cross-sectional survey Choi & Ko, (2023) suggested that social factors (social activities, living arrangements, emotional support, etc.) attenuated the association between CF and disability, supporting interventions to improve contact and support, and in longitudinal analyses, Wang et al (2022) found that social support and psychological distress were both associated with CF after one year, social support reducing the negative effect of psychological distress. Rivan et al (2019) also found that lower social support independently predicted CF, alongside depression, age and poorer activities of daily living.…”
Section: Social Network: Social Engagement Social Support and Lonelinessmentioning
confidence: 73%
“…In a cross-sectional survey Choi & Ko, (2023) suggested that social factors (social activities, living arrangements, emotional support, etc.) attenuated the association between CF and disability, supporting interventions to improve contact and support, and in longitudinal analyses, Wang et al (2022) found that social support and psychological distress were both associated with CF after one year, social support reducing the negative effect of psychological distress. Rivan et al (2019) also found that lower social support independently predicted CF, alongside depression, age and poorer activities of daily living.…”
Section: Social Network: Social Engagement Social Support and Lonelinessmentioning
confidence: 73%
“…Loneliness can reflect social support to some extent. However, Wang et al found that psychological distress could regulate the relationship between social support and the prevalence of CF [ 17 ]. Therefore, the relationship between mental state and CF remains vague and requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…A review shows that social status, nutrition status, physical and cognitive activities and functional status are factors shown to be associated with CF [ 15 ]. However, the effect of depression in CF remains controversial and we need to explore future [ 16 , 17 ]. Social support has been shown to be an influential factor for CF in hypertensive patients [ 18 ] and other studies have found the effects of BMI and nutrition status of CF [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The baseline survey was completed in June 2019, which was considered prior to the COVID-19 pandemic on the basis of the declaration from the World Health Organization on March 11, 2020, that COVID-19 can be characterized as a pandemic [32]. The detailed study design, sampling, and data collection have been described elsewhere [2,33,34]. Briefly, we used the multistage stratified random sampling method to select participants, excluding those who had a clinical diagnosis of dementia or psychiatric diseases, could not complete the interview due to severe physical conditions, or were unwilling to cooperate with the interviewers.…”
Section: Study Design and Data Sourcesmentioning
confidence: 99%